Sada Sabai Dance in Komering Culture of East OKU Regency - Aditia Candra Buana, Ika; Hartono, Hartono; Triyanto, Triyanto (Catharsis, 2020)
Sada Sabai dance as one of South Sumatra's traditional art works, especially in East Ogan Komering Ulu Regency is very closely related to Komering culture. Sada Sabai dance is one of the characteristics of the Komering culture that dwells in the South Sumatra region, created based on the spirit of the Komering community when holding a traditional wedding ceremony. Sada Sabai dance is one form of art that is used by many Komering people who are presented during the traditional wedding ceremony. The problem raised in this study aims to analyze the characteristics of the Sada Sabai dance that developed in the Komering culture. The method used is a qualitative method with a case study research design. Data collection techniques include observation, interview and document study. The results showed that Sada Sabai dance was a symbol of the harmony between the bride and groom family, so that in the past Sada Sabai dance was only danced by married families. This phenomenon was clearly seen when the groom's family and the bride danced on the stage how the two of them looked very close to each other. Then, the movement in Sada Sabai dance emphasized improvisation and exploration as its main approach and the main characteristic lied in the middle fingers of the dancers.